The Spiralling of Corporate Corruption and the Plummeting of Corporate Governance and Ethical Leadership in African Institutions - Hlalele Matebese (African Journal of Political Science)
Generally, several factors around the corporate world influence different nations technologically, socially, economically, and politically. Specifically, this paper focuses on the African continent’s politics concerning corporate corruption, corporate governance, and ethical leadership. This study aims to critically reflect on and evaluate the significance of curbing and combating corruption, promoting governance and ethics in Africa, and furthering and practising those principles. It employed a theoretical, qualitative content analysis approach in which a critical evaluation of relevant in-depth literature review was used and conducted to achieve the study objective. The results of this study revealed that: Incompetent and unethical leaders succumb to corruption, causing Africa's corruption to spiral out of control. Competent and ethical leaders, on the other hand, resist corruption; African leaders and authorities should take steps to fight corruption through ethics and governance; African corporations have become increasingly corrupt; corporate governance and ethical leadership have declined in Africa; African politicians have uncurbed power to advance their private gains, and finally, African leaders need to change their mindsets and cultures to achieve economic growth. This study emphasizes and reiterates the importance of dealing effectively with corporate corruption and advancing governance and ethics to benefit the African population and the continent. It further provides a broad and deeper understanding of corruption, ethics, and governance. The conceptual, strategic model provided by this study may be selected and used by African leaders, authorities, boards of directors, shareholders, and Chief Executive Officers (CEOs), as a tool to address corruption in African organizations and institutions.